Description of Dryocosmus destefanii new species (Hymenoptera: Cynipidae: Cynipini) from Quercus suber L. in Italy - Cerasa, Giuliano; Verde, Gabriella Lo; Caleca, Virgilio; Massa, Bruno; Nicholls, James A.; Melika, George (Zootaxa, 2018)
A new species, Dryocosmus destefanii Cerasa & Melika n. sp. associated with a Cerris section oak, Quercus suber L., is described from Italy. Description, diagnosis, host associations and biology for the new species and an illustrated identification key to the Western Palaearctic Dryocosmus species are given. The description is supported by morphological and molecular data.